2008
DOI: 10.2118/98237-pa
|View full text |Cite
|
Sign up to set email alerts
|

High-Viscosity-Yield Acid Systems for High-Temperature Stimulation

Abstract: This paper discusses the development of a unique in-situ crosslinkable acid system that uses a blend of hydrochloric acid (Hcl)/ formic acid as the base acid and a synthetic polymer gelling agent. The ability to in-situ crosslink an organic acid blend is novel. In addition, an unexpected result of the fluid development was the discovery of its unique rheological properties.Historically, both gelled and in-situ-crosslinked acids have been used for fluid-loss control during fracture acidizing and for diversion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The effect of formic and acetic acids on the viscosity of live in-situ-gelled acids was investigated by van Domelen and Jennings (1995). The authors showed that increasing formic acid concentration increased the viscosity of the live acids, and they related that increase to the stability that organic acids add to the polymer at higher temperatures (van Domelen and Jennings 1995; Welton and van Domelen 2008). This claim is confirmed by the results shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The effect of formic and acetic acids on the viscosity of live in-situ-gelled acids was investigated by van Domelen and Jennings (1995). The authors showed that increasing formic acid concentration increased the viscosity of the live acids, and they related that increase to the stability that organic acids add to the polymer at higher temperatures (van Domelen and Jennings 1995; Welton and van Domelen 2008). This claim is confirmed by the results shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Several laboratory and field studies have been reported also in the literature (Buijse et al 2004;Chang et al 2008). Welton and van Domelen (2008) evaluated gelled and in-situcrosslinked HCl/formic-acid blends equivalent to 28 wt% HCl and claimed that HCl and formic acid can be successfully crosslinked in situ. They observed that some synthetic polymer/acid gelling agents provide high initial viscosity in HCl/formic acid blends and stated that the gelled HCl-formic acid blends are more robust (than HCl blends) and maintain higher viscosities for longer periods at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed for 5 minutes while maintaining a nitrogen pressure of 1,100-1,150 psig in the reaction vessel to keep CO2 in solution and maintain a singlephase fluid (Welton and Domelen 2008;Nasr-El-Din et al 2008;Taylor and Nasr-El-Din 2009). Samples of acid (3 cm 3 ) were withdrawn from the reaction vessel every minute, and the sampling line was purged with air after each sample was withdrawn to prevent sample contamination.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The reason for the low permeability of the reservoir could be due to two reasons: one is that the reservoir is a naturally low permeability reservoir (II reservoir); the second is that the permeability of oil reservoirs are reduced owing to the pollution close to the well in the process of oil and gas development. [1][2][3][4] These unprocessed segments mean that production will be reduced and a certain amount of the reserves will be lost. Therefore, retarded acid technology is applied to give deep acidication in order to improve the effect of acid treatment, see Fig.…”
Section: Introductionmentioning
confidence: 99%